Procedural justice, anger, and prisoners’ misconduct: a longitudinal study - Beijersbergen, Karin A. (Criminal justice and behavior, 2015)
Procedural justice literature suggests that when criminal justice authorities treat people with fairness and respect, people will be more likely to comply with authority?s decisions and rules. Up until now, prior research has largely neglected the correctional context and often used cross-sectional designs. The aims of this study were to examine (a) the longitudinal relationship between prisoners? procedural justice perceptions and their misconduct, and (b) the mediating role of anger in this relationship. Using two waves of survey data (T1 and T2) and disciplinary reports from a sample of 806 Dutch prisoners, structural equation models were employed to investigate associations. The results show that prisoners who felt treated in a procedurally just manner in the correctional facility at T1 were less likely to report engaging in misconduct at T2. They were also less likely to have received a disciplinary report at T2. Anger fully mediated the effect of procedural justice on prisoners? misconduct.